ANALISIS KETERAMPILAN BERPIKIR KREATIF DALAM PENGERJAAN SOAL MATEMATIKA SISWA KELAS IV - Siti Nuranisah Siregar (Institute of Educational, Research, and Community Service, 2023)
The aim of this research was to examine the creative thinking skills in mathematics of grade IV students at SDN 192 Pekanbaru, especially in the context of Geometry and multiplication operations. Mathematics is known as a universal language that has significant relevance in various aspects of life. In the context of mathematics, creative thinking skills are the key to approaching problems using innovative methods and creating alternative solutions. In mathematics, understanding and developing creative thinking skills is considered valuable in improving students' understanding of Geometry and multiplication operations. This study uses quantitative research methods and measures students' creative mathematical thinking skills through tests that include indicators such as elaboration, fluency, flexibility, and originality. From this observation, results were obtained which stated that the creative thinking abilities of class IV students were quite adequate overall. However, authenticity indicators were found to be underdeveloped. In conclusion, mathematics learning needs to place more emphasis on the elaboration of students' creative thinking skills, especially in the context of Geometry and multiplication operations, to increase students' understanding and enthusiasm for learning.